Kepadatan Benih Ikan Komet (Carracius auratus) Pada Pemeliharaan Sistem Resirkulasi - Muhammad Sugihartono; Muarofah Ghofur; Feryn Deanita (Universitas Batangahari Jambi, 2023)
The purpose of this study was to determine the most optimal density of komet fish (C. Auratus) fry in rearing with a recirculation system. This study used a completely randomized design (RAL) with 4 treatments and 3 replications where the treatments were : treatments A : stocking density 1 fish/L, treatments B : stocking density 3 fish/L, treatments C: stocking density 5 fish/L and treatments D : stocking density 7 fish/L. Parameters observed were survival rate, absolute weight growth (PBM), absolute length growth (PPM), and blood glucose. The results showed that the average survival rate of komet fish was 99,62%, average PBM was 0,48 g/fish, average PPM was 1,47 cm/fish and blood glucose was 34,50-39,33 mg/dl. The best density for rearing komet fish was 1 fish/L.